Molecular Characterization and Expression Analysis of TaZFP15, a C2H2-Type Zinc Finger Transcription Factor Gene in Wheat (Triticum aestivum L.) - Zhao-hua SUN; Chang-huan DING; Xiao-juan LI; Kai XIAO (Journal of Integrative Agriculture, 2012)
Based on sequencing of part clones in a root subtractive cDNA library, an expressed sequence tag (EST) sharing high similarity to a rice C2H2 zinc finger transcription factor (ZFP15) was obtained in wheat. Through bioinformatics approach, the wheat C2H2-type ZFP gene referred to TaZFP15 has been identified and characterized. As a full-length cDNA of 670 bp, TaZFP15 has an open reading frame of 408 bp and encodes a 135-aa polypeptide. TaZFP15 contains two C2H2 zinc finger domains and each one has a conserved motif QALGGH. The typical L-box, generally identified in the C2H2 type transcription factors, has also been found in TaZFP15. Phylogenetic analysis suggested that TaZFP15 shares high similarities with rice ZFP15 (GenBank accession no. AY286473), maize ZFP (GenBank accession no. NM_001159094) and a subset of other zinc-finger transcription factor genes in plant species. The expression of TaZFP15 was up-regulated by starved-Pi stress, showing a pattern to be gradually elevated along with the progression of the Pi-stress in a 23-h treatment regime. Similarly, the transcripts of TaZFP15 in roots were also induced by nitrogen deficiency, and abiotic stresses of drought and salinity. No responses of TaZFP15 were detected in roots to nutrition deficiencies of P, Zn, and Ca, and the external treatment of abscisic acid (ABA). TaZFP15 could be specifically amplified in genome A, B, and D, and without variability in the sequences, suggesting that TaZFP15 has multi-copies in the homologous hexaploid species. Transgenic analysis in tobacco revealed that up-regulation of TaZFP15 could significantly improve plant dry mass accumulation via increasing the plant phosphorus acquisition capacity under Pi-deficiency condition. The results suggested that TaZFP15 is involved in mediation of signal transductions of diverse external stresses.